2013
DOI: 10.5114/jcb.2013.34338
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided brachytherapy (IGBT) combined with whole pelvic intensity-modulated radiotherapy (WP-IMRT) for locally advanced cervical cancer: a prospective study from Chiang Mai University Hospital, Thailand

Abstract: PurposeA report of preliminary results and toxicity profiles using image-guided brachytherapy (IGBT) combined with whole pelvic intensity-modulated radiation therapy (WP-IMRT) for locally advanced cervical cancer.Material and methodsFifteen patients with locally advanced cervical cancer were enrolled into the study. WP-IMRT was used to treat the Clinical Target Volume (CTV) with a dose of 45 Gy in 25 fractions. Concurrent cisplatin (40 mg/m2) was prescribed during radiotherapy (RT) on weekly basis. IGBT using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…These findings also strengthens earlier observations of maximum doses to both bladder and rectum higher than corresponding ICRU reference points and the significance of doses to OAR which can be estimated by three dimensional image based brachytherapy (Fellner et al, 2001;Kim et al, 2003). Combination of image based brachytherapy and intensity-modulated radiotherapy can also improve dose distribution in target volume and overdose to organs at risk (Tharavichitkul et al, 2013). Few studies have concluded that in centers where MRI based brachytherapy is not feasible due to logistics reasons, OAR and target may be contoured with CT which gives comparable results to MRI for dose volume estimation if clinical findings and baseline MRI findings are applied in contouring of CT images (Eskander et al, 2010;Krishnatry et al, 2012 observed MRI is being used by 20% for planning (Gueda et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…These findings also strengthens earlier observations of maximum doses to both bladder and rectum higher than corresponding ICRU reference points and the significance of doses to OAR which can be estimated by three dimensional image based brachytherapy (Fellner et al, 2001;Kim et al, 2003). Combination of image based brachytherapy and intensity-modulated radiotherapy can also improve dose distribution in target volume and overdose to organs at risk (Tharavichitkul et al, 2013). Few studies have concluded that in centers where MRI based brachytherapy is not feasible due to logistics reasons, OAR and target may be contoured with CT which gives comparable results to MRI for dose volume estimation if clinical findings and baseline MRI findings are applied in contouring of CT images (Eskander et al, 2010;Krishnatry et al, 2012 observed MRI is being used by 20% for planning (Gueda et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…Again, the CT-trial inclusion and exclusion criteria were reused maintaining the study focus on large cervical tumors (FIGO IIB n = 12, IIIB n = 3), and the established brachytherapy constraints for HR-CTV and OARs (see first and second UCP major projects) were re-adopted. This study reconfirmed the prior findings of significant OARs dose reduction in bladder ( p < 0.001), rectum ( p = 0.001), and sigmoid ( p < 0.001), and maintained a high curative HR-CTV total dose (mean EQD2: 88 Gy) [ 27 ].…”
Section: Third University Cooperation Platform Major Project – Combinsupporting
confidence: 88%
“…Patients with documented grade 3 toxicities received slightly higher cumulative doses to the clinical target volume. The observed difference in toxicity may be attributable to the benefit of volume-optimized dosimetric planning associated with image-based treatment and IMRT use, which have been shown to minimize radiation dose to organs at risk [2527]. No grade 4 or 5 toxicity was observed.…”
Section: Discussionmentioning
confidence: 99%